Efficacy of lidocaine versus mepivacaine in the management of myofascial pain - Hamad Albagieh; Ashwag Aloyouny; Nojoud Alshehri; Noor Alsammahi; Dima Almutrafi; Emad Hadlaq (Elsevier, 2020)
Objectives: There are many treatment modalities for myofascial pain, and recent findings reported in the literature highlight the superiority of using local anesthetics as the treatment of choice. The objective of the present study was to compare the effectiveness of two of the most used local anesthetic agents-lidocaine and mepivacaine-in the management of myofascial pain. Materials and methods: Thirty patients (20 females, 10 males) were randomly assigned to one of two groups: 50% received lidocaine and 50% received mepivacaine. Trigger point injections in the orofacial region were administered 4 times, 10 days between each injection, with 4 weeks of follow-up after the end of the treatment course. Pain levels were recorded using a visual analog scale (VAS) at the time of follow-up and 30 min after injection. Results: All patients exhibited statistically significant improvement when comparing pre- and post-treatment mean values. Both local anesthetics (i.e., lidocaine and mepivacaine) were similarly effective for the management of myofascial pain (p = 0.875). The mepivacaine-treated group exhibited significantly lower post-injection tenderness than the lidocaine group (p = 0.038). There was no relationship between sex and treatment response. Female and male patients both reported similar responses in terms of VAS scores (p = 0.818). Conclusion: No drug was superior in the long term; thus, the clinician's choice can be based on drug availability and patient medical history.